Pengembangan Bahan Ajar Menulis Cerpen Dengan Model Pembelajaran (PJBL) Untuk Kelas Ix - Era Octafiona; Edi Suyanto; Muhammad Fuad (Universitas Lampung, 2018)
This study aims (1) produce products in the form of short story textbook with (PjBL) models for grade IX, and (2) test and describe the feasibility of textbook writing short stories with (PjBL) models developed based on experts material, media, peers, and students.This research adapts development research Borg and Gall.This research was conducted at three schools in Bandar Lampung including Junior High School of 13, Junior High School of Baitul Jannah, and Junior High School of Global Madani in the academic year 2017/2018. (PjBL) models contained in this teaching material, among others, formulating basic questions, designing planning, scheduling, monitoring, testing results, and evaluating activities.The results of this study (1) produce teaching materials in the form of